MANAJEMEN KEPALA MADRASAH DALAM MENGEMBANGKAN MADRASAH DIGITAL DI MTs NEGERI 6 PASURUAN - Dewi Fayruz Safitri; M. Ma'ruf (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2025)
Management is a benchmark for the quality of education so that good education can be seen from how the madrasa head manages his madrasa. Likewise with digital madrasas, it is always related to how the madrasa head is managed and it is time for madrasas to follow the era which is now completely digital. This research aims to find out how the madrasa head manages in developing digital madrasas at MTs Negeri 6 Pasuruan. This research method uses qualitative observation and interviews conducted at MTs Negeri 6 Pasuruan. The results of this research are that madrasah heads are able to manage digital madrasah development by planning by determining mission, targets, strategies and budgets. Then through organizing by dividing performance related to digital madrasas according to the portion of human resource capabilities at MTs Negeri 6 Pasuruan. Then in terms of implementation both in learning and human resources. The final evaluation is both in terms of learning, social media and infrastructure. So, madrasa head management is very important in developing digital madrasas.